KONTRIBUSI OBJEK WISATA PANTAI CAROCOK PAINAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN PESISIR SELATAN PROVINSI SUMATERA BARAT - Iranti Ranggeni; Hamdi Hamid; Lamu Lamu (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was supposed to find out how was the increation of Pantai Carocok Turism’ Contributies that affected by tourist attraction, amenities, facilities and infrastructure and also acommodation development which led to increasing visitor amount significantly every years. Tourism revenue is the largest source of regional income in Pesisir Selatan Regency, one of the tourism objects that provide the greatest contribution to the Original Revenue is a Pantai Carocok Tourism. Analysing data by using descriptive analysis, research method using survey method, the data needed is secondary data with data source is the Department of Tourism and the Office of Revenue and Management of Finance and Regional Assets (DPPKAD). Judging from Pantai Carocok Painan tourism revenue data, tourism contribution consisting of contribution of hotel, restaurant, tourist attraction, ticket sales and parking area of Pantai Carocok area can contribute on average from 2012-2016 as much as 5,51% from Local Own Revenue Pesisir Selatan Regency where the highest contribution of the object occurred in the year 2016 that is as much as 8,02% and the tourism sector contributes the most is the entrance fee of Pantai Carocok area is 2.4%. Keyword : Contribution, Tourism, Pantai Carocok Painan